QUALITY IMPROVEMENT STUDIES ELECTRICITY AND REDUCTION OF LOSSES IN POWER LINES (Web of Technology: Multidimensional Research Journal, 2024)
The article explores the possibility of using an IGCT thyristor (with an integrated gate) in high-current high-power rectifier systems and STATCOM voltage converters together with series-connected control devices for longitudinal compensation-controlled voltage source CVS that regulate power flows.